4-1BB signaling beyond T cells - Vinay, Dass S (Nature Publishing Group, 2011)
Originally discovered as a T cell-activating molecule, 4-1BB (CD137) is now also recognized as an activator of non-T cells, thus imparting a new dimension to its potential in vivo effects. 4-1BB expression is seen on a variety of non-T cells including activated dendritic cells (DCs), monocytes, neutrophils, B cells and natural killer (NK) cells, and promotes their individual effector functions. The T cell- and non-T cell-activating ability of 4-1BB may be the basis of its powerful anti-cancer, anti-autoimmune and anti-viral effects. Here we discuss the consequence and importance of 4-1BB signaling in non-T cells. We consider its effects on immune regulation, and the distinct and/or overlapping pathways involved in these responses, as well as possible therapeutic applications.